(untitled) (Molecular Medicine Communications, 2023)
It has been known that there exists a connection between oxidative stress, ribosomal dysfunction, and the metabolic decline observed in conditions such as obesity and aging. The ribotoxic stress response (RSR) is a signaling pathway in which the p38- and ZAKα sense stalling and/or collision of ribosomes. ZAKα, also known as MAP3K20, is a mitogen-activated protein kinase kinase kinase (MAP3K) that plays a role in cellular signaling pathways. Snieckute and colleagues show that reactive oxygen species (ROS)-generating agents trigger ribosomal impairment and ZAKα activation. They also found that ZAK-knockout mice are protected from developing high-fat high-sugar (HFHS) diet-induced blood glucose intolerance and liver steatosis, stressing the role of the RSR in metabolic regulation. Their study revealed the hallmarks of metabolic aging in animals after ZAK ablation. Understanding these molecular pathways could provide insights into the cellular mechanisms contributing to metabolic dysfunction in these conditions and may potentially lead to the development of targeted interventions or therapies. Science 2023 Dec 8;382(6675):eadf3208. doi: 10.1126/science.adf3208.